Effect of Low-Level Laser Therapy on Bone Regeneration in Midpalatal Suture after Rapid Maxillary Expansion - Furkan Dindaroğlu; Gökhan Önçağ; Sultan Ölmez; Servet Doğan; Özlem Gümrükçü-Ertürk (Galenos Yayinevi, 2011)
Aim:The aim of this study is to evaluate the effects of low level laser therapy (LLLT) on bone regeneration in the midpalatal suture after rapid maxillary expansion.Subjects and Methods:The study sample comprised thirteen patient aged between 10 and 15 years old with maxillary transverse deficiency (> 5 mm) and bilateral or unilateral posterior crossbite were included. All patients underwent rapid maxillary expansion with the use of Hyrax expander and subjects were divided into 2 groups: control group (n=15) and laser group (n=15). The patient's parents were instructed to activate Hyrax expander by turning the screw one turn in the morning and another turn in the evening. A diode laser (3 W, = 810 nm, 9=3,5 cm2) was used. The laser was applied in 5 sessions with intervals of 48 hours. The laser was applied in continuous mode and for the 15 seconds at each point. The delivered energy was 45 j and energy density was 13 j/cm2. The laser probe was placed behind the singulum of incisors. Multi-slice low dose Computer tomography scans were taken 1,5 months later after final laser application in laser groups and 3 months later in control group. Density was measured in Hounsfield unit.Results:The difference in bone density of midpalatal suture between control and laser group was not statistically significant (p > 0.05). Bone density in midpalatal suture of two sample groups is almost equal as Hounsfield Unit.Conclusion:Low level laser therapy shortens retention period, accelerates bone regeneration in midpalatal suture during rapid maxillary expansion. Evaluated in terms of bone ossification in the median suture, 3 months of stability could be achieved after 1.5 months. Low level laser application after rapid maxillary expansion can play an active role on the retention time and stability.